2013
DOI: 10.1177/0192623313503519
|View full text |Cite
|
Sign up to set email alerts
|

HIV Treatment and Associated Mitochondrial Pathology

Abstract: Antiretroviral therapy has dramatically reduced mortality in human immunodeficiency virus (HIV) infection. In 1988, the suggestion that the first antiretroviral drug, zidovudine, was the potential cause of muscle pathology in HIV-infected persons resulted in structural and biochemical patient studies demonstrating acquired mitochondrial dysfunction. Assessment of subsequent nucleoside analog reverse transcriptase inhibitor (NRTI) antiretroviral drugs has indicated that mitochondria are a common target of NRTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(39 citation statements)
references
References 74 publications
(86 reference statements)
1
38
0
Order By: Relevance
“…Similarly, the antiviral role of mitochondria in human infectious diseases has been given more and more attention in recent years [14,15]. Mitochondria are a common target of nucleoside analog reverse transcriptase inhibitor (NRTI) toxicity in multiple tissues during HIV treatment with NRTI antiretroviral drugs [16]. Overall, it appears that drug addiction and HIV treatment interact with mitochondria in many different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the antiviral role of mitochondria in human infectious diseases has been given more and more attention in recent years [14,15]. Mitochondria are a common target of nucleoside analog reverse transcriptase inhibitor (NRTI) toxicity in multiple tissues during HIV treatment with NRTI antiretroviral drugs [16]. Overall, it appears that drug addiction and HIV treatment interact with mitochondria in many different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Other specific medications, currently in use, have been shown to produce serious adverse reactions. It should be noted that there have been observed more Grade 4 Events (Lifethreatening Events) due to (Ganta et al, 2017;Yu et al, 2017;Fortuny et al, 2015;Sun et al, 2014;Zhang et al, 2014;Gardner et al, 2014;Liu et al, 2013;Patel et al, 2012;Hulgan and Gerschenson, 2012;Vidal et al, 2011). The medication used for treating HIV with HAART (High Activity Antiretroviral Therapy)-than those of AIDS itself (Reisler et al, 2003).…”
Section: Specific Medicationmentioning
confidence: 99%
“…The SMART study found that episodic ART guided by CD4 count, compared to a continuous ART regimen, was associated with a hazard ratio for CVD events of 1.6 (95 % CI 1.0-2.5) [59]. However, it is possible that long-term ART may increase CVD risk through several mechanisms, including the induction of mitochondrial toxicity and excess oxidative stress, dyslipidemia, insulin resistance, and changes in body composition [51,52,54,60]. Nucleoside reverse transcriptase inhibitors (NRTIs) downregulate mitochondrial DNA polymerase, leading to decreased mitochondrial DNA replication [54].…”
Section: Inflammationmentioning
confidence: 99%
“…However, it is possible that long-term ART may increase CVD risk through several mechanisms, including the induction of mitochondrial toxicity and excess oxidative stress, dyslipidemia, insulin resistance, and changes in body composition [51,52,54,60]. Nucleoside reverse transcriptase inhibitors (NRTIs) downregulate mitochondrial DNA polymerase, leading to decreased mitochondrial DNA replication [54]. The inability of mitochondria to function properly causes oxidative stress [54].…”
Section: Inflammationmentioning
confidence: 99%
See 1 more Smart Citation